KONTRIBUSI KECERDASAN EMOSIONAL DAN KECERDASAN INTERPERSONAL TERHADAP GAYA KEPEMIMPINAN PENGURUS SANGGAR SENI DI KOTA PEKANBARU - RAFIUD DRAJAD; DAENG AYUB NATUNA; MAKHDALENA MAKHDALENA (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The aim of this research was to find out the contribution of theemotionalintellegence and social intellegence either simultaneously or partiall on caretaker leadershipstyle of art galleries in the city of Pekanbaru. The population of the research was member ofart galleries in the City of Pekanbaru. Totalling 240member, with sample of 100 activememberusing cluster random samplingtechnique. Form data in this study are primary andsekunder. Data collection through questionnairefor art of leadership, emotional intellegence,social intellegence.Data using likert scale. Metods of data analysis in this study multiple regressionSPSS. Research result showed that:1)emotional intellegence has a high interpretations, 2)socialintellegence has a high interpretations, 3)style of leadership has a high interpretations,4)simultanaeously and partially contained a significant and strong relathionship between emotionalintellegence and social intellegence to the leadership style, 5)simultanaeously and partiallycontained a significant and great contribution between emotional intellegence and socialintellegence to the leadership style.